Ahli Waris Pengganti Di Indonesia Dengan Historisitasnya - Muhamad Sauki Alhabsyi; Syahrul Mubarak Subeitan (Indonesian Journal of Shariah and Justice, 2021)
The case of inherition is one of the areas specifically regulated in Islamic law, both the determination of who is entitled (dzawil furudh, ashabah, and dzawil arham) and the details of the number of divisions in the Qur'an. However, with the times came problems and issues of "contemporary" heirs including the issue of replacement heirs. In the books of fiqh or books written by Islamic jurists do not recognize the designation of a replacement heir or the change of position of a replacement heir (plaatvervulling) as mentioned in Article 185 compilation of Islamic law. This is a deconstruction of public opinion in Islamic inherited law. This research then highlights the historical aspect of the presence of Surrogate Heirs in inheritance law in Indonesia, using a library research model with historical deepening of the application of a law.